The Dream about the Battle of Berezina in Dostoevsky’s Novel White Nights - Nikolay N. Podosokorsky (Достоевский и мировая культура: Филологический журнал)
The article examines the Battle of Berezina in the Patriotic War of 1812 as one of the significant historical and literary dreams of the Dreamer’s story in Dostoevsky’s early sentimental novel White Nights. The list of dreams of the hero of White Nights — which includes, in addition to the Battle of Berezina, St. Bartholomew’s Night, a heroic role in the capture of Kazan by Tsar Ivan IV Vasilyevich, the burning of Jan Hus in Constance, Danton, Cleopatra and her lovers, a house in Kolomna, etc. — was added by Dostoevsky to the text of the novel during its revision in 1860. It is argued that this list cannot be reduced to the writer’s autobiography and identified with the similar list from the feuilleton Petersburg Dreams in Verse and Prose (1861), nor it is correct to strictly divide it into purely literary and historical elements. It is proved that Dostoevsky’s hero looks at world history as an artist and poet, mainly through the prism of art, and his interest in tragic and bloody events, executions and murders, is due not to pathological cruelty, but to the desire to transform these perversions of the human spirit into stories of human compassion and empathetic participation. Special attention is paid to possible sources of the hero’s dreams about the Battle of Berezina: Honoré de Balzac’s short story Farewell! (1830), the historical novel by R.M. Zotov Borodino core and Berezinskaya ferry (1844), etc. In addition, an attempt is made to describe the hidden Napoleonism of the Dreamer, who, like Dostoevsky, was born in the year of Napoleon’s death.